Minat Dan Motivasi Peternak Untuk Mengembangkan Ternak Sapi Pada Kawasan Perkebunan Kelapa Sawit di Propinsi Jambi - H, Afriani; Idris, Nahri; F, Fatati (Fakultas Peternakan Universitas Jambi, 2014)
Â The survey method was used to conduct this study through 180 cow farmers in three Regencies (merangin, Muaro Jambi and West tanjung Jabung) in Jambi Province. Samples of farmer were choised as the Simple Random sampling. Results of this study showed that farmer interest to rare cows within palm oil plantatition area in Jambi Province looked high with the interest value of 82.24% and the motivation of farmer to grow cow was medium with the value of 77.56%. Â The analysis of multiple linear regression indicated that interest and motivation can be explained together with variable measured (area, the age of oil palm tree, farmer experience, livesock enterprise scale, income, the amount of family member and group activity). The interest and motivation value of farmer to grow cow were 37 and 45.20% respectively. The F test showed that the regression model could be usedto predict interest and motivation of farmer to grow cows as the level of significant of less than 0.05. There was highly significant effect between group activity and motivation and significant effect between age of tree, farmer experience, and group activity with farmer interest and motivation.